1994
DOI: 10.1007/bf03403527
|View full text |Cite
|
Sign up to set email alerts
|

Role of Macrophage Oxidative Burst in the Action of Anthrax Lethal Toxin

Abstract: Background: Major symptoms and death from systemic Bacillus anthracis infections are mediated by the action of the pathogen's lethal toxin on host macrophages. High levels of the toxin are cytolytic to macrophages, whereas low levels stimulate these cells to produce cytokines (interleukin-1(3 and tumor necrosis factor-a), which induce systemic shock and death. Materials and Methods: Experiments were performed to assess the possibility that the oxidative burst may be involved in one or both of lethal toxin's ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 21 publications
0
71
0
Order By: Relevance
“…These include interleukins and interferons. The main cytokines involved in this discussion are interleukin-1-beta and tumor necrosis factor-alpha [6,7]. This sophisticated defense system, however, teeters on a precarious balance because the same molecules (reactive oxygen and nitrogen intermediates and cytokines) produced by the macrophages in defense against invading organisms also have the potential to cause serious damage and destruction of the macrophages themselves.…”
Section: Anthraxmentioning
confidence: 98%
See 3 more Smart Citations
“…These include interleukins and interferons. The main cytokines involved in this discussion are interleukin-1-beta and tumor necrosis factor-alpha [6,7]. This sophisticated defense system, however, teeters on a precarious balance because the same molecules (reactive oxygen and nitrogen intermediates and cytokines) produced by the macrophages in defense against invading organisms also have the potential to cause serious damage and destruction of the macrophages themselves.…”
Section: Anthraxmentioning
confidence: 98%
“…This sophisticated defense system, however, teeters on a precarious balance because the same molecules (reactive oxygen and nitrogen intermediates and cytokines) produced by the macrophages in defense against invading organisms also have the potential to cause serious damage and destruction of the macrophages themselves. Furthermore, if excessive amounts of these molecules escape into the extracellular space and general circulation, they can also cause severe damage and in ammation in distant tissues and ultimately cause systemic shock and death [6,7]. Normally, this potential for self-injury/destruction is well compensated for by an elegant built-in self-protection system, whereby the macrophage (a) simultaneously produces its own free radical scavenger/antioxidant molecules and associated enzyme catalysts, such as glutathione, glutathione peroxidase, and superoxide dismutase; (b) tightly regulates the synthesis/inhibition signaling governing the production and release of these 'double-edged sword' molecules; (c) restricts them to subcellular locales where their effects can be tolerated [6,7].…”
Section: Anthraxmentioning
confidence: 99%
See 2 more Smart Citations
“…Hanna et al [129] found that cultured macrophages treated with LeTx release superoxide anion at about the time that cell lysis begins, and that macrophage lysis could be prevented by the addition of anti-oxidants. When LeTx resistant cell lines were examined, they were found to be deficient in the production of reactive oxygen intermediates (ROIs).…”
Section: Review Articlementioning
confidence: 98%